A Review of Analytical Methods for Codeine Determination - Pratiwi, Rimadani; Noviana, Eka; Fauziati, Rizky; Carrão, Daniel Blascke; Gandhi, Firas Adinda; Majid, Mutiara Aini; Saputri, Febrina Amelia (Molecules (Basel, Switzerland), 2021)
Codeine is derived from morphine, an opioid analgesic, and has weaker analgesic and sedative effects than the parent molecule. This weak opioid is commonly used in combination with other drugs for over-the-counter cough relief medication. Due to the psychoactive properties of opioid drugs, the easily obtained codeine often becomes subject to misuse. Codeine misuse has emerged as a concerning public health issue due to its associated adverse effects such as headache, nausea, vomiting, and hemorrhage. Thus, it is very important to develop reliable analytical techniques to detect codeine for both quality control of pharmaceutical formulations and identifying drug misuse in the community. This review aims to provide critical outlooks on analytical methods applicable to the determination of codeine.